2019
DOI: 10.3390/foods8020062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Biogenic Amines on Food Quality and Safety

Abstract: Today, food safety and quality are some of the main concerns of consumer and health agencies around the world. Our current lifestyle and market globalization have led to an increase in the number of people affected by food poisoning. Foodborne illness and food poisoning have different origins (bacteria, virus, parasites, mold, contaminants, etc.), and some cases of food poisoning can be traced back to chemical and natural toxins. One of the toxins targeted by the Food and Drug Administration (FDA) and European… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
310
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 415 publications
(318 citation statements)
references
References 95 publications
1
310
0
7
Order By: Relevance
“…There are many reasons to prevent the accumulation of BAs in fermented products, mainly related to their utility as food quality indicators and their potential implications for consumer health. Controlling these compounds implies a deep understanding of the formation, monitoring and reduction of BAs during the processing and storage of food, and even of the effects of BAs in consumers after the digestion of foods containing different levels of these compounds (Ruiz-Capillas & Herrero, 2019). The presence of BAs in a substrate is dependent both on contamination by decarboxylating microorganisms, on the availability of precursors (proteins and/or FAA), and on different intrinsic, environmental, and technological factors (Gardini et al, 2016).…”
Section: Formation Of Bas In Barley By-products During Their Treatmmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reasons to prevent the accumulation of BAs in fermented products, mainly related to their utility as food quality indicators and their potential implications for consumer health. Controlling these compounds implies a deep understanding of the formation, monitoring and reduction of BAs during the processing and storage of food, and even of the effects of BAs in consumers after the digestion of foods containing different levels of these compounds (Ruiz-Capillas & Herrero, 2019). The presence of BAs in a substrate is dependent both on contamination by decarboxylating microorganisms, on the availability of precursors (proteins and/or FAA), and on different intrinsic, environmental, and technological factors (Gardini et al, 2016).…”
Section: Formation Of Bas In Barley By-products During Their Treatmmentioning
confidence: 99%
“…Bas are harmful substances generated during the fermentation process. Controlling these compounds implies a deep understanding of the formation, monitoring and reduction of BAs during the processing and storage of food, and even of the effects of BAs in consumers after the digestion of foods containing different levels of these compounds(Ruiz-Capillas & Herrero, 2019). There are many reasons to prevent the accumulation of BAs in fermented products, mainly related to their utility as food quality indicators and their potential implications for consumer health.…”
mentioning
confidence: 99%
“…They also protect the bacteria against radiations and oxidative stress and participate in biofilm formation, in the development of mechanisms of antibiotic resistance and in pathogenesis (Maeda et al, 2006;Patel et al, 2006;Kwon and Lu, 2007;Shah and Swiatlo, 2008;Williams et al, 2010). It has been reported recently that certain amines generated by commensal gut microbes are involved in molecular signalling and are related to different syndromes (depression, anxiety, psychosis), highlighting the importance of the 'microbial-gut-brain' axis (Oleskin and Shenderov, 2019;Ruiz-Capillas and Herrero, 2019;Sudo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many nitrogen containing organic compounds that could be considered as BAs, in this review, we will only focus on study of the compounds indicated in Fig. 1 which are defined by many authors as classical BAs (Smith, 1981;ten Brink et al, 1990;Arias et al, 2008;Arcos et al, 2010;de la Torre et al, 2018;Barbieri et al, 2019;Ruiz-Capillas and Herrero, 2019;Sudo, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation